Macroeconomic Policies New Issues of Interdependence - Reisen, Helmut (OECD Development Centre Working Papers, 2005)
Three novel macroeconomic policy challenges are discussed in this paper: the macroeconomic implications of China's emergence; the implications of intensifying financial integration; and the interaction of Asia's foreign exchange regime with monetary policy in the OECD area. First, China may now be regarded as a price maker on some international commodity and energy markets. Its global impact nowadays stretches importantly not just into goods and commodity markets, but equally into world financial markets. The acquisition by the Chinese official sector of large amounts of foreign assets has raised the country's global cyclical, financial and macroeconomic importance. Hence, China should not just be perceived as a producer of low-priced goods, but likewise of "cheap savings". China as a swing exporter/importer could destabilise commodity markets, with important repercussions for developing countries. Variations in China's output gap will have important repercussions on key global ...